Humans and other commonly used model organisms are resistant to cycloheximide-mediated biases in ribosome profiling experiments - Puneet Sharma (Nature Portfolio, 2021)
Ribosome profiling has become the gold standard to analyze mRNA translation dynamics, and the translation inhibitor cycloheximide (CHX) is often used in its application. Here the authors systematically demonstrate that CHX does not bias the outcome of ribosome profiling experiments in most organisms.